Strategi Pengembangan UMKM Kota Bengkulu Di Era Ekonomi Digital - Indraswanti, Bertha Iin Esti; Sunoto, Sunoto (Universitas Bengkulu, 2024)
The purpose of this research was to determine Bengkulu MSEs strategy in digital economy era. The most of MSEs were conventional management. Its due to not only the millennial businessmen, but the most of them is from the baby boomer generation. The use of technology has not yet become a culture, so the challenge more difficult with millennial consumers and more competitive with millennial businessman. The result from SWOT analysis is the weakness more than the strenghts and the opportunities has more than the threats. The strategy to develop MSEs is stability strategy (turn around). The strategies are: easier access to financial institution (bank), increasing socialization and simplification of lending requirements, conduct training of tehnology, digital payment system and e-commerce, provide assistance in administrative completeness, implementation of promotion events regularly. Keywords : Micro Small Enterprises, Strategy, Digital Economy Abstrak Tujuan penelitian ini adalah untuk menentukan strategi Bengkulu SME di era ekonomi digital. Sebagian besar SME adalah manajemen konvensional. Hal ini disebabkan tidak hanya oleh para pengusaha milenial, tetapi sebagian besar dari mereka berasal dari generasi baby boomer. Penggunaan teknologi belum menjadi budaya, sehingga tantangan lebih sulit dengan konsumen milenial dan lebih kompetitif dengan pengusaha millenial. Hasil dari analisis SWOT adalah kelemahan lebih dari kekuatan dan peluang lebih dari ancaman. Strategi untuk mengembangkan SME adalah strategi stabilitas (turn around). Strategi-strategi tersebut adalah: memfasilitasi akses ke lembaga keuangan (bank), meningkatkan sosialisasi dan menyederhanakan persyaratan pinjaman, melakukan pelatihan teknologi, sistem pembayaran digital dan e-commerce, memberikan bantuan dalam kelengkapan administrasi, implementasi acara promosi secara teratur. Kata Kunci : Micro Small Enterprises, Strategi, Ekonomi Digital